Transformation Design and Human-Machine Scale Adaptability of Office Furniture in the Post-epidemic Era - Sun, Jialin (International Scientific Technical and Economic Research, 2025)
In the post-pandemic era, the office environment has undergone profound changes, with flexible and remote working becoming mainstream work styles. With the diversification of working methods and changes in office space, the fixed design of traditional office furniture can no longer meet the needs of modern offices. This article explores the transformable design and ergonomic adaptability of office furniture in the post-pandemic era, focusing on how transformable design can improve furniture flexibility and space utilization, and the importance of ergonomics in furniture design. By analyzing outstanding office furniture cases both domestically and internationally, this article showcases innovative applications of transformable design and ergonomics, and based on user feedback, evaluates the effectiveness of these designs in actual use. The study found that the combination of transformable design and ergonomics can help improve the comfort, functionality, and adaptability of office furniture, but in practical application, it still faces challenges such as design complexity, stability, and personalized needs. Finally, the article looks forward to future trends in office furniture design, proposes development directions in terms of intelligence, personalization, and environmental protection, and provides theoretical basis and practical guidance for subsequent research.